2024
DOI: 10.1146/annurev-psych-013123-102139
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Goals: A Social Influence Cycle

Fabrizio Butera,
Benoît Dompnier,
Céline Darnon

Abstract: Achievement goals have been defined as the purpose of competence-relevant behavior. In this respect they connect one of the basic human needs, i.e., competence, to one of society's core values, i.e., achievement. We propose to look at achievement goals through the lens of social influence. We review both the influence that cultural, structural, and contextual factors have on achievement goal endorsement and the influence that endorsing achievement goals allows people to have within their social space. The revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Thus, interacting with popular coworkers changes this cost/benefit calculation, leading PPGO individuals to overweight the costs of sharing knowledge with popular coworkers. Indeed, previous studies have also shown that PPGO individuals are relatively less constructive than LGO individuals in social situations [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, interacting with popular coworkers changes this cost/benefit calculation, leading PPGO individuals to overweight the costs of sharing knowledge with popular coworkers. Indeed, previous studies have also shown that PPGO individuals are relatively less constructive than LGO individuals in social situations [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As organizations undergo extensive flattening through organizational restructuring, employees’ interactions with their coworkers become more immediate and frequent [ 26 ], leading to interdependence and an increased frequency of communication. More than ever, coworkers have become organizations’ most salient resources with whom employees interact [ 57 , 58 ]. Our study provides additional empirical evidence of the importance of coworkers in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be very useful in the early stages of research on a new mechanism, but in the present research, we were working with one of the most researched cooperative classroom methods-the jigsaw classroom-and wanted to observe what the effect would be if a nationwide educational policy was introduced. Indeed, interventions in the educational domain may be hampered when they are at odds with teachers' beliefs (Yeager et al, 2022), and-more specifically with cooperative learning-when students are not prepared to appreciate the importance of cooperation (Buchs et al, 2016) or when cooperation is promoted in otherwise competitive educational structures (Butera et al, 2021(Butera et al, , 2024. Our results showed that the jigsaw classroom has the potential to reduce the gender gap in social competences, even in the face of the extreme variability of implementation that necessarily occurs in real-life classrooms.…”
Section: Contributionsmentioning
confidence: 99%
“…Beyond these cognitive sources, the bias toward inherent explanations is reinforced by cultural ideas and institutional features of school contexts. In European and North American cultural contexts, the pervasive idea that a person is an independent, autonomous entity (e.g., Markus & Kitayama, 1991) may exacerbate the tendency to explain behavior as the result of the person's own characteristics (Butera et al, 2021(Butera et al, , 2024Plaut & Markus, 2005;Stephens et al, 2009). In the context of schooling, cultural ideas such as equal opportunity and meritocracy (e.g., Darnon, Smeding, & Redersdorff, 2018;Duru-Bellat & Tenret, 2012) also imply that observed differences in performance correspond to inherent differences in effort and ability.…”
Section: The Inherence Bias In Explanationmentioning
confidence: 99%